Exosomes orchestrate immune homeostasis in acute ischemia-reperfusion flap injury and chronic wounds: the TLR4/NF-κB-STAT3 R-ratio balance decision model, engineering optimization and translational clinical strategy - Qin Yue; Jinhao Chen; Lin Liu; Hui Liu; Xinyi Zeng (Frontiers in Immunology, 2026)
Flap ischemia-reperfusion injury (IRI) and chronic refractory wounds are intractable clinical challenges in the field of wound repair. Both pathological conditions share a core pathological hallmark: disrupted homeostasis of the local wound inflammatory immune microenvironment, yet they exhibit distinct patterns of inflammatory dysregulation. Mesenchymal stem cell-derived exosomes exert bidirectional immunomodulatory effects. They inhibit the TLR4/NF-κB signaling pathway to alleviate the acute inflammatory storm triggered by IRI, whereas they activate the STAT3 pathway to reinitiate tissue repair in chronic wounds. Nevertheless, a unified theoretical framework explaining the environment-dependent functional switch of exosomes remains absent in current research, hindering the development and clinical translation of targeted engineered exosomes. To fill this research gap, we perform a systematic review integrating five pivotal inflammatory signaling pathways, including TLR4/NF-κB, STAT3, TGF-β/Smad, NLRP3 and MAPK. We establish a TLR4/NF-κB-STAT3 signal ratio balance decision model to uniformly interpret inconsistent findings from existing in vitro and in vivo experiments. This model verifies that the concentrations of inflammatory cytokines, oxidative stress levels, and immune cell subsets within the wound microenvironment coordinately regulate the activation intensity ratio (R value) of the TLR4/NF-κB and STAT3 pathways, which ultimately determines whether exosomes exert anti-inflammatory or pro-repair effects. Unlike conventional strategies that only enhance a single therapeutic function, the proposed model provides quantitative evidence for the targeted design of microenvironment-adaptive intelligent exosomes. This review further summarizes standardized quality control protocols and stratified clinical trial designs for exosomes, objectively discusses the limitations of current translational research, and puts forward multiple verifiable follow-up experimental hypotheses. Collectively, this work constructs a comprehensive theoretical framework for precise immune regenerative therapies targeting flap IRI and chronic wounds.